Fiscal Decentralization and Corruption: The Facts in Regional Autonomy in Indonesia - SUPRAYITNO, Bambang; PRADIPTYO, Rimawan (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
There are tricky effects of fiscal decentralization on corruption both in concept and empirical studies. This study aims to determine the influence of fiscal decentralization on corruption in local level (provinces) governments in Indonesia. Using the Supreme Court (Mahkamah Agung) cassation, in 2001-2009, this research applies econometric method exactly Tobit model to provide the evidence utilizing modified model of Yardstick Competition. Result shows that the higher the level of fiscal decentralization will increase corruption. Population also increases corruption. Detection rate from neighbor area could hit the corruption. State official salary level, GDP per capita, and literacy rates and dummy variables of special autonomy do not affect corruption. Rich areas have lower levels of corruption than the poor. Areas outside Java-Bali (non Greater Jakarta) have an average lower corruption than corruption in the area on the island of Java and Bali. The Greater Jakarta has higher corruption than others.